INTEGRATIVE APPROACH TO THE USE OF TWO-STAGE DENTAL IMPLANTATION IN PATIENTS WITH COMPLETE JAW ADENTIA - Axmedov Alisher Astanovich; Jalolov Sharifjon Rahmonovich (American Journals, 2023)
The use of dental implants for orthopedic treatment of patients with primary and secondary periodontal diseases has become increasingly common in recent years [1-3]. The continuous further development of dental implant systems, professional development of specialists and the growth of the competence of dental laboratories ensured the success and confidence of this approach. However, its success undoubtedly depends on the proper planning and conduct of the surgical stage and the subsequent manufacture of the prosthesis. The integrity of this process and the constant interaction between the orthopedist, the surgeon and the dental technician are crucial [2]. Completely toothless maxillary and mandibular patients or partially toothless patients with an unfixed bite (without antagonistic tooth contact) are a particular problem for a specialist in dental implant rehabilitation. Difficulties in these clinical situations arise both at the stage of surgical implant placement and at the stage of prosthetics [1, 3, 5]. In order to improve the method of two-stage dental implantation in fully and partially toothless patients with an unformed bite, a comprehensive method was proposed using full or partial prostheses at all stages of implantation: from preparation for surgery to the creation of a permanent orthodontic structure.